2021
DOI: 10.3390/sym14010012
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Effect of Symmetry on Velocity of the Four Swimming Strokes?

Abstract: The different characteristics of the four swimming strokes affect the interplay between the four limbs, acting as a constraint to the force produced by each hand and foot. The purpose of this study was to analyze the symmetry of force production with a varying number of limbs in action and see its effect on velocity. Fifteen male swimmers performed four all-out bouts of 25-m swims in the four strokes in full-body stroke and segmental actions. A differential pressure system was used to measure the hands/feet pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Seifert et al [ 77 ] concluded that asymmetries in arm coordination might be due to different roles between limbs (propulsion and rhythm for the dominant upper arm vs. propulsion and compensation for breathing laterality for the non-dominant upper arm). Bartolomeu et al [ 78 ] have hypothesized that swimming is probably a task that benefits up to a certain extent, from some asymmetry, possibly above 10%. In the present study, the mean LSI was about 96%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seifert et al [ 77 ] concluded that asymmetries in arm coordination might be due to different roles between limbs (propulsion and rhythm for the dominant upper arm vs. propulsion and compensation for breathing laterality for the non-dominant upper arm). Bartolomeu et al [ 78 ] have hypothesized that swimming is probably a task that benefits up to a certain extent, from some asymmetry, possibly above 10%. In the present study, the mean LSI was about 96%.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, literature has reported the same lack of meaningful correlation. Power output and hand force symmetries were not correlated to performance in tethered swimming [ 30 ] and free swimming [ 78 ], even when high asymmetries were present. The reason behind these findings can, yet again, be underpinned by the different roles of both limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a differential pressure system composed of two hand sensors has been proposed as a reliable method to estimate the resultant force of both hands [10] without imposing any constraints on young swimmers' mechanics or efficiency [11]. However, a paucity of information remains about the understanding of young swimmers' forces retrieved directly as most of the swimmers tested were above 15 years of age [3,12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using the differential pressure method reported the measurement of in-water forces using two (e.g., Pereira et al, 2015 ; Bartolomeu et al, 2022 ) or four to eight sensors (e.g., Takagi and Wilson, 1999 ; Koga et al, 2020 ) in swimming strokes. Despite the number of sensors in play, the Aquanex System (a two-hand set-up) showed to be an easy-to-use procedure without encompassing a heavy set-up.…”
Section: Introductionmentioning
confidence: 99%
“…The peak and mean forces retrieved by this pressure sensors system have been regularly used to understand acute responses to different stimulus (e.g., Morais et al, 2020 ), the relationship to swimming velocities (e.g., Bartolomeu et al, 2022 ), upper-limb imbalances (e.g., Morais et al, 2020 ), or warm-up effects (e.g., Barbosa T. M. et al, 2020 ). Both kinetic variables appear to be highly reliable in young swimmers when using the tethered-swimming method ( Amaro et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%